Implications and size of trade in anti-infective drugs a.u.v. and About the drafting of medical and veterinary ordinances in Romania - Romeo T. Cristina (Medicamentul Veterinar, 2023)
The presentation brings information about the developments in the trade with veterinary products, comparative, in the world, in Europe and in Romania in the light of the One - Health approach, the evolution of the relevant legislation, up to EU Regulation 2019/6 and its implementation. Data are presented on the counterbalancing of commercial trends related to veterinary medicines which, from the preponderance towards farm animals, are slowly moving towards companion animals. Here, too, a projection of the global pharmaceutical products market is made, as well as the slice allocated to a.u.v. products, the global portfolio allocated to animal health, the current situation in Romania as well as the main global producers of veterinary drugs. In the second part of this presentation, there is a reminder of new medical orders according to the current legislation, as well as an example of how to write the ATC-vet electronic ordinance (Anatomical - Therapeutical - Chemical).